EFEKTIFITAS ROSATIN (ROMPI SASAK PIJAT OKSITOSIN) TERHADAP PRODUKSI ASI IBU MENYUSUI - Saudia, Baiq Eka Putri; Marliana, Yunita; Rofita, Desi (Politeknik Kesehatan Kemenkes Mamuju, 2025)
The World Health Organization (WHO) recommends exclusive breastfeeding during the first six months of an infant’s life. Breast milk provides numerous benefits to infants, such as protection against gastroenteritis, respiratory infections, ear infections, urinary tract infections, allergies, diabetes mellitus, sudden infant death syndrome (SIDS), and obesity, and it can also enhance cognitive development. However, many mothers face challenges in breastfeeding due to insufficient breast milk production. The production of breast milk itself is often a key inhibiting factor in successful breastfeeding. Optimal breastfeeding practices play a critical role in reducing stunting among children under five, aligning with both global and national targets to reduce stunting by 40 percent. One non-pharmacological therapy commonly used by health workers or therapists to address breastfeeding difficulties is oxytocin massage. In this study, the researchers developed a novel, previously untested non-pharmacological tool called ROSATIN (Sasak Oxytocin Massage Vest). ROSATIN integrates the traditional fabric of the Sasak tribe into a vest designed to stimulate oxytocin points along the spine, mimicking the effects of manual oxytocin massage by providing gentle, targeted pressure and promoting maternal relaxation. This study aims to evaluate the effectiveness of the ROSATIN tool in increasing breast milk production among breastfeeding mothers. A quasi-experimental design with a two-group post-test-only approach was employed. The intervention group received massage using ROSATIN, while the control group received a traditional oxytocin massage performed by a trained therapist. The study involved 60 breastfeeding mothers who reported irregular breast milk production. Participants were selected using purposive sampling. Data were analyzed using the Wilcoxon test, while effectiveness was assessed through the N-Gain score. The results showed a significant increase in breast milk production in both groups following the intervention, with a significance value of 0.000 (p< 0.05). However, the effectiveness test revealed that massage using ROSATIN demonstrated higher effectiveness, with an N-Gain score of 0.844, compared to manual massage by a therapist.